Amplification of tick-borne encephalitis virus infection during co-feeding of ticks - Labuda, M; Danielova, V; Jones, L D; Nuttall, P A (Medical and veterinary entomology, 1993)
Following engorgement of Rhipicephalus appendiculatus larvae on guinea-pigs infected with tick-borne encephalitis (TBE) virus, none of the engorged larvae or emergent nymphs contained detectable infectious virus. However, one of twelve pools, each containing three of the unfed nymphs, was positive when screened by polymerase chain reaction (PCR), indicating a low prevalence of TBE virus infection in the unfed nymphs. After engorgement of the nymphs on four uninfected guinea-pigs, 19/24 (79%) fed nymphs from one guinea-pig and 4/25 (16%) fed nymphs from a second guinea-pig were infected; all the ticks examined from the other two guinea-pigs were uninfected. The results suggest that TBE virus was transmitted from a low proportion of infected nymphs (infected as larvae) to uninfected nymphs as they fed together on an uninfected guinea-pig. Such amplification of the initial infection, at the population level, could play an important role in maintaining TBE virus infections in nature, particularly if there is a low level of vertical transmission from one tick generation to the next.
Keywords: RNA, Viral; RNA virová; polymerázová řetězová reakce; Male; klíšťata; replikace viru; Guinea Pigs; Nymph; Ticks; Encephalitis Viruses, Tick-Borne; Arachnid Vectors; mužské pohlaví; Encephalitis, Tick-Borne; Viral Plaque Assay; arachnida jako vektory; nymfa; larva; Animals; lidé; Virus Replication; Humans; zvířata; klíšťová encefalitida; morčata; myši; viry klíšťové encefalitidy; Polymerase Chain Reaction; Larva; plakové testy; Mice